2009
DOI: 10.1016/j.ydbio.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous turning of cerebellar granule cells in vitro by intrinsic programs

Abstract: External guidance cues play a role in controlling neuronal cell turning in the developing brain, but little is known about whether intrinsic programs are also involved in controlling the turning. In this study, we examined whether granule cells undergo autonomous changes in the direction of migration in the microexplant cultures of the early postnatal mouse cerebellum. We found that granule cells exhibit spontaneous and periodical turning without cell-cell contact and in the absence of external guidance cues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…At the middle and bottom of the EGL, granule cells had a horizontally oriented soma with two horizontally extending processes (a leading process and a trailing process) ( Fig. 1 A and B) (13,14). To monitor granule cell migration in the EGL, a small amount of 1,1′-dioctadecyl-3,3,3′,3′ tetramethylindocarbocyanine perchlorate (DiI) solution was injected into the EGL of lobules V, VI, and VII of the cerebellum (Fig.…”
Section: Speed Of Granule Cell Migration In Vivo Depends On Light-darkmentioning
confidence: 99%
See 1 more Smart Citation
“…At the middle and bottom of the EGL, granule cells had a horizontally oriented soma with two horizontally extending processes (a leading process and a trailing process) ( Fig. 1 A and B) (13,14). To monitor granule cell migration in the EGL, a small amount of 1,1′-dioctadecyl-3,3,3′,3′ tetramethylindocarbocyanine perchlorate (DiI) solution was injected into the EGL of lobules V, VI, and VII of the cerebellum (Fig.…”
Section: Speed Of Granule Cell Migration In Vivo Depends On Light-darkmentioning
confidence: 99%
“…During the last 2 decades, real-time observation of cell movement demonstrated that granule cells display a distinct mode, tempo, and rate of migration as they traverse different cortical layers (13)(14)(15)(16)(17). It became apparent that granule cell migration is controlled by the orchestrated activity of multiple molecular events at the right time and right place, including pathway selection, activation of specific receptors and channels, and assembly and disassembly of cytoskeletal components (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Although it is known that the appearance of granule cells using Golgi-staining is sporadic (Ono et al, 1997; Kumada et al, 2009), we assumed that the frequency of Golgi-stained granule cells with a particular morphological feature among the total Golgi-stained granule cells reflected the proportion of granule cells with the same morphology in the early postnatal mouse cerebella. We also assumed that the application of ethanol does not affect the efficiency of the Golgi-staining.…”
Section: Methodsmentioning
confidence: 99%
“…To attain their proper position, neurons are required to change their direction of movement at the right time and place during the journey towards their destination (Ramón y Cajal, 1929; Rakic, 1990; Yacubova and Komuro, 2003; Britanova et al, 2006; Kawauchi et al, 2006; Tanaka et al, 2006; Kumada et al, 2007; Nakajima, 2007; Cameron et al, 2007, 2009a; Kumada et at, 2009; Komuro et al, 2010). For example, in the developing cerebellum, postmitotic granule cells first migrate tangentially at the middle of the external granular layer (EGL) for 20–30 hours (Komuro et al, 2001; Komuro and Yacubova, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Kumada et al [59] reported that the autonomous turning of cerebellar granule cells, that can be observed in vitro, is dependent on both calcium influx (through voltage dependent and NMDA channels) and release from intracellular stores: stimulating the release through ryanodine receptors with caffeine (1 mM) or the IP3 receptors with the agonist thimerosal (5 µM) strongly increased the frequency of turning events.…”
Section: Calcium Release From Intracellular Storesmentioning
confidence: 99%